Menentukan Metode Terbaik Implementasi Enterprise Architecture: Analisis Perbandingan Metode TOGAF dan FEAF - Citra Adinda Hartawan; Azmina Zata Ismah; Elis Kholisoh; Mulyanah Mulyanah; Reny Agustina Hasugian; Ali Idrus (INTECH, 2024)
This research explores the implementation of Enterprise Architecture (EA) with a focus on two main methods, namely The Open Group Architecture Framework (TOGAF) and the Federal Enterprise Architecture Framework (FEAF). EA implementation is recognized as the key to integrating business strategy and information technology in organizations. TOGAF offers a structured approach with clear phases, while FEAF is more focused on the government sector with more general guidelines. TOGAF is known for its comprehensive coverage and global support, while FEAF has advantages in the United States government context. Comparative analysis identifies the advantages and disadvantages of both. TOGAF has complexities that can be a challenge, while FEAF may be suboptimal for complex private organizations. The research conclusion highlights that the choice of method depends on the needs and context of the organization. TOGAF may be better suited to a structured and comprehensive implementation, while FEAF may be quicker to implement with a more limited focus. This research provides guidance for decision makers in selecting EA methods that suit the unique characteristics and goals of the organization.